Efficacy of an external volume expansion device and autologous fat grafting for breast reconstruction following breast conserving surgery and total mastectomy: Small improvements in quality of life found in a prospective cohort study. Issue 1 (January 2020) - Howes, Benjamin H.L.; Watson, David I.; Fosh, Beverley; Dean, Nicola R.
Summary: Background: Although autologous fat grafting (AFG) for breast reconstruction is feasible, the best methods have yet to be established. This study aimed to assess the efficacy of fat grafting using an external expansion device for complete breast reconstruction post breast cancer surgery hypothesizing that it would improve quality of life. Methods: A prospective cohort study was conducted in women who had undergone breast cancer surgery and complete reconstruction using AFG. An external expansion device was used previously (as per Miami protocol) to a single-stage AFG. Quality of life outcomes were determined using the validated BREAST-Q questionnaire, and 3D laser and magnetic resonance imaging scan were used to measure fat graft retention. Results: Twenty-six participants were recruited, with seven withdrawing. The remaining 19 women were compliant with external expander use. The mean volume of AFG was 270.4 mL (98–490 mL) with a mean of 48.8% retained at 12 months following injection. Symmetry improved but did not meet the acceptable symmetry ratio of 0.8. Nine patients (47.3%) noted increased skin elasticity and softening of areas of scarring. Skin irritation occurred in 11 out of 19 patients. Mean BREAST-Q scores improved significantly in the domains of satisfaction with breast (40 vs. 49, p < 0.001), psychosocial well-being (55 vs. 68, p < 0.001), physical well-being abdomen (73 vs. 87, p < 0.001), and sexual well-being (41 vs, 48, p < 0.001). Conclusion: Improved quality of life and breast volume increase were achieved following external expansion and AFG. However, breast fat engraftment retention was similar to that reported in previous studies using fat grafting alone.